Experimental study of thermo-physical properties and application of paraffin-carbon nanotubes composite phase change materials - Wu, XueHong; Wang, ChunXu; Wang, YanLing; Zhu, YouJian (International journal of heat and mass transfer, 2019)
•Composite phase change materials are prepared and the thermophysical properties are test.•The carbon nanotubes filled into paraffin can increase the thermal conductivity of Composite phase change materials.•Composite phase change materials are applied into VORDC to improve the temperature uniformity. In order to improve the thermal conductivity of pure paraffin (RT4) which is regarded as cool storage of phase change material (PCM), four kinds of paraffin-carbon nanotubes cool storage of composite PCMs are prepared by adding different amount of carbon nanotube (CNT) into paraffin, and their thermo-physical properties are tested by using differential scanning calorimeter (DSC) and laser thermal conductivity meter. The results show that, with the increasing of carbon nanotubes, the phase transition temperature of the cool storage of composite PCMs diminishes, phase change latent heat dwindles while thermal conductivity gradually increases. Compared with the pure paraffin, increase in mass fraction of carbon nanotube 3% can provide an increase in thermal conductivity of the solid and liquid 30.3% and 28.5%, and a reduce in the melting and solidification phase change latent heat of composite PCM 8.9% and 9.3%, respectively. Further investigation applies the composite PCMs into the shelf of vertical open -type refrigerated display cabinet to improve the performance. The results show that the shelf filled with the composite PCMs can decrease the internal temperature of the VORDC and temperature fluctuation during the defrosting period. Compared with the ordinary shelf, the lengthways and depthwise temperature different of composite shelf filled into only RT4 reduce by 80.0% and 7.6%, respectively; the lengthways and depthwise temperature different of composite shelf filled into 3%-CNT composite PCMs reduce by 92.0% and 12.2%, respectively. It indicates that the composite PCMs further increases the thermal conductivity of composite shelf and improve the performance of VORDC.